Designing for product sound quality. - Lyon, Richard H., ....- (New York : Dekker, 2000)
"Provides previously unavailable material in sound quality crucial for a more effective design process. Presents all aspects of product sound quality, such as "rules of thumb" and design formulas and charts. Covers sound radiation and targeting, resolving, and testing design features."
Keywords: Geluidsbeheersing; Industriële vormgeving; Ontwerpen